The Prognosis of Breast Cancer: A Comparison of Different Neural Network Architectures - Hamdan, H.; Taib, N.M.; Kareem, S.A.; Har, Y.C. (2004)
Artificial neural networks are useful tools for solving many real-world problems and are usually utilized for complex data analysis. In the field of medicine, artificial neural networks have been used since the late 1980s, initially as an aid to diagnosis and treatment, and lately as a tool for the analysis of survival data. The main advantage of a neural network is its ability to generalise to new situations based on existing patterns. This advantage is used as a basis to compute and predict the survival of individual cases. This paper describes the research on the application of artificial neural networks in the prognosis of breast-cancer based on the cases seen in the University of Malaya Medical Centre from the year 1993 to 2002